Prediction of parameters of microscale coating-metal interface phase based on finite element method. (October 2019) - Jia, Z K; Zhang, Y; Xin, J H; Cheng, Q
Abstract: The coating-metal transition interface can form a stable gradient interface phase composite. In this paper, a finite element model of gradient interface phase is established based on Tyson Polygon Method (TPM), and the microstructure equivalent parameters of interface material of the element are obtained by means of average method. By analyzing the functional relationship between the equivalent elastic parameters of the gradient interface element and the metal volume ratio, the functional expression of the microstructure parameter distribution of the interface phase is obtained. The results show that the equivalent elastic modulus and equivalent shear modulus of the interface satisfy the distribution of exponential function, linear function and power function in the local scope. The change rule of equivalent Poisson's ratio with metal phase volume fraction in local scope can be expressed by logistic function. It is found that the global parameter distribution of interface phase is different from that of local material. The equivalent elastic modulus and equivalent shear modulus of the global interface satisfy the double exponential function distribution, while the distribution law of the equivalent Poisson's ratio can be piecewise expressed by the logistic function and the exponential function.